The RNA-Binding Protein RBM3 Promotes Neural Stem Cell (NSC) Proliferation Under Hypoxia - Yan, Jingyi; Goerne, Tessa; Zelmer, Andrea; Guzman, Raphael; Kapfhammer, Josef P.; Wellmann, Sven; Zhu, Xinzhou (Frontiers in Cell and Developmental Biology, 2019)
Neural stem cells (NSCs) reside physiologically in a hypoxic niche to maintain self-renewal and multipotency. Whereas mild hypoxia is known to promote NSC proliferation, severe hypoxia in pathological conditions exerts reverse effect. The multi-functional RNA-binding protein RBM3 is abundant in NSCs and can be regulated by hypoxic exposure. Although RBM3 has been shown to accelerate cell growth in many cell types, whether and how it affects NSC proliferation in hypoxic environment remains largely unknown. In this study, we tested how RBM3 regulates cell proliferation under hypoxia in C17.2 mouse NSC cell line and in primary mouse NSCs. Our results demonstrated that RBM3 expression was highly sensitive to hypoxia, and NSCs were arrested in G0/G1 phase by 5% O2, 2.5% O2 and 1% O2 treatment. When we overexpressed RBM3, hypoxia-induced cell cycle arrest in G0/G1 phase was relieved and more cell transit into S phase was observed. Furthermore, cell viability under hypoxia was also increased by RBM3. In contrast, in RBM3-depleted primary NSCs, less BrdU-incorporated cells were detected, indicating exacerbated cell cycle arrest in G1 to S phase transition. Our findings indicate RBM3 as a potential target to maintain the proliferation capacity of NSCs under hypoxia, which can be important in NSC-based therapies of acute brain injury and chronic neurodegenerative diseases.